Effects of Authentic Assessment Practices on Students’ Skill Acquisition in TVL-HE Bread and Pastry Production: A Quasi-Experimental Study - Guevarra, Ronafe; Birj, Melba (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of Authentic Assessment Practices on the psychomotor skill acquisition of Grade 12 Technical-Vocational-Livelihood Home Economics students specializing in Bread and Pastry Production at Dolores National High School during the 2025–2026 academic year. Anchored on Experiential Learning Theory and Situated Cognition, the study used a quasi-experimental pre-test–post-test non-equivalent control group design involving 46 students. The Control Group consisted of 21 students assessed through traditional written testing, while the Experimental Group consisted of 25 students assessed through performance-based tasks, industry-aligned analytical rubrics, and continuous formative feedback. Data were gathered using a Psychomotor Skill Acquisition Diagnostic Tool and an Industry-Aligned Analytical Rubric validated by Home Economics master teachers and TESDA-certified assessors. Results showed that both groups improved significantly from pre-test to post-test; however, the Experimental Group achieved a higher post-test mean score of 86.56 compared with the Control Group’s mean score of 68.43. The independent-samples t-test revealed a significant difference between the groups, with an exceptionally large effect size, indicating that authentic assessment had a stronger effect on students’ skill acquisition. The study concludes that authentic assessment strengthens technical competence, product quality, safety practices, operational pacing, and readiness for workplace immersion or national qualification assessment. The study supports SDG 4 on Quality Education, SDG 8 on Decent Work and Economic Growth, SDG 9 on Industry, Innovation and Infrastructure, and SDG 17 on Partnerships for the Goals. Its sustainability impact lies in improving educational quality, strengthening employability, reducing vocational grade inflation, and aligning school-based assessment with industry standards.